Triple luminescent center energy transfer enables color tuning in Na3Y(PO4)2:RE3+ (RE = Tb/Eu/Tm) for w-LEDs. (1st October 2022) - Wu, Xiulan; Zhao, Xinlong; Ren, Qiang; Du, Liang; Pei, Mengkang; Hai, Ou
Graphical abstract: A single matrix phosphor of Na3 Y(PO4 )2 : xTb 3+, yEu 3+, zTm 3+ crystallizes in the Pca 21 orthorhombic system. The color can be adjusted from green (0.308, 0.587) to red (0.578, 0.378) by co-doping Tb 3+ -Eu 3+, which has the potential for application in color display LED. The mechanism of energy transfer is characterized as electric dipole-electric dipole interaction. After the blue emission of Tm 3+ is introduced, light waves of different colors are emitted at different excitation wavelengths. The color coordinates of (0.338, 0.342) can be achieved in the triple luminescence center by adjusting the concentration of Tm 3+, which is very close to the standard white light emission. The single-phase white-light-emitting phosphor has specific application potential in the field of w-LEDs. Abstract: Single-phase host white light-emitting materials have been widely favored by researchers recently because of their advantages, such as no color reabsorption, better CRI, coordinated CCT, and pure CIE chromaticity coordinates. In this paper, a single matrix phosphor of Na3 Y(PO4 )2 : xTb 3+, yEu 3+, zTm 3+ was prepared by the high-temperature solid-state method, and white light emission was obtained by color regulation. The synthesized phosphor crystallizes in the Pca 21 orthorhombic system, and the doping of rare-earth ions will not affect the phase composition. Firstly, the fluorescence properties of Na3 Y(PO4 )2 : Tb 3+ are studied. Tb 3+ has high doping quenching concentration and shows a typical narrow-band green emission peak caused by the f-f transition. The color can be adjusted from green (0.308, 0.587) to red (0.578, 0.378) by co-doping Tb 3+ -Eu 3+, which has the potential for application in color display LED. The mechanism of energy transfer is characterized as electric dipole-electric dipole interaction. After the blue emission of Tm 3+ is introduced, light waves of different colors are emitted at different excitation wavelengths. The color coordinates of (0.338, 0.342) can be achieved in the triple luminescence center by adjusting the concentration of Tm 3+, which is very close to the standard white light emission. The single-phase white-light-emitting phosphor has specific application potential in the field of w-LEDs.